Content Validity Of A Self-Reported Instrument For Safety And Health (S&H) Culture Practice In Paramedic Training Institute Using A Heterogeneous Expert Panel (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Background: Although there is comprehensive coverage of studies conducted in safety and health management, practice, and performance, there is a limited study focusing on health professionals in paramedic training institutions which can be considered a low-risk workplace setting. Besides selecting heterogenous experiential experts in assessing new instruments', to our knowledge, the content validity on the topic has not been well described in the literature. Hence, the purpose of this study was to describe the use of experiential experts in a content validity evaluation of a new self-reported questionnaire to determine the safety and health culture practice in paramedic training institutes.Methods: This study involved two phases, instrument design and judgemental evidence. A panel of nine experts was involved in validating this questionnaire. They were five experiential industrial safety and health specialist, and four professional occupational health researchers or trainers. The quantitative content validity index (CVI), Item-CVI (I-CVI), and Scale-level CVI (S-CVI) were used to make decisions on items in the instrument whether to retain or remove the items.Results: Results showed good content validity of individual items (I-CVI range: 0.70 to 1.00) and excellent overall scale content validity (S-CVI = 0.97). There were 44 initial items, and the item was accepted when it obtained a minimum score of at least 0.80. Most of the items were retained (n = 42), and only two were eliminated, which was considered not relevant by the judges. Five dimensions have been identified, safety and health system (five items), safety and health risk management (four items), safety and health competency (three items), safety and health management/supervision (ten items), and worker involvement in safety and health (three items).Conclusion: Good content validity index from an expert view of each item's content and relevance to be included as a safety and health culture practice indicator for paramedic training institute. Although a new instrument's content validity seems costly in terms of time and human resources, its value deserves more attention in developing valuable and valid assessment tools.